Application and theory of petri nets and concurrency : 40th international conference, PETRI NETS 2019, Aachen, Germany, June 23–28, 2019, proceedings /: 40th international conference, PETRI NETS 2019, Aachen, Germany, June 23–28, 2019, proceedings. (2019) - Unknown
No abstract available